Determinants of consumers' purchasing intention for Nakhom Pathom community products / Nur Zainie Abd Hamid and Mohamed Samsudeen Sajahan - Abd Hamid, Nur Zainie; Sajahan, Mohamed Samsudeen (2019)
The study of consumers will help businesses to improve their marketing strategies by understanding issues such as how consumers think and feel, how the consumer is influenced by the environment and the behaviour of consumers while making marketing decisions. However, identifying potential consumers is a crucial element in the marketing process. Products can no longer be manufactured and sold without taking into account consumer needs and wants. Today, consumers decision-making has become more complex and complicated. This is due to the rapid change of the competitive global business environment in which consumers are being exposed to a range of products information and the increasing number and choices of goods. In this case, understanding consumer decision-making is very important for marketers in coming up with appropriate marketing strategies to suit their target groups. Many factors have been identified in the literature on the theme of consumer shopping behaviour as a significant element in understanding consumer purchase intention. The factors have become fundamental indicators for marketers to meet their consumers' needs and wants. Therefore, marketers should always strive to understand the differences and similarities in consumers decision-making styles. Nakhon Pathom community has targetted to export its products among Malaysian. Such international business is one of the most crucial marketing elements for many businesses. In this relation, understanding Malaysian consumer behaviours and purchase intention are important for the Nakhon Pathom community to develop strategies to target Malaysian. This study, therefore, intends to examine the determinants of consumers' purchasing intention in Malaysia towards Nakhon Pathom community products.